Nitrogen doped carbon quantum dots as Co-active materials for highly efficient dye sensitized solar cells. (15th October 2021) - Shejale, Kiran P.; Jaiswal, Arun; Kumar, Aditya; Saxena, Sumit; Shukla, Shobha
Abstract: High-quality nitrogen-doped carbon quantum dots (NCQDs) are synthesized using domestic microwave-assisted pyrolysis method. These show excellent physiochemical and optical properties such as wide spectral adsorption, high charge carrier extraction, fast charge carrier transportation, and tuneable emission. These NCQDs are introduced in the dye sensitized solar cell (DSSC)/quantum dot sensitized solar cell (QDSSC) structure to improve the performance. The effect of synthesized NCQD as sensitizer, co-sensitizer, and co-photoactive layers is investigated for the DSSC/QDSSC structure. High photoconversion efficiency of 8.75% and photocurrent density of 18.13 mA/cm 2 is achieved under one sun irradiation when NCQDs are used as co-photoactive layer. The obtained power conversion efficiency is approximately 55% and 99% better than NCQDs as co-sensitizer and sensitizer, respectively. The incorporation of the NCQDs in the photoactive layer synergically enhanced photo absorbance and reduced recombination between photoanode and electrolyte. A large number of anchoring sites for dye, highly conducting photoanode, fast charge carrier transportation, and inherent light-emitting photo-fluorescent property of NCQDs in mesoporous titania are understood to be responsible for this enhancement. The optimized weight ratio of citric acid and urea in the synthesis of NCQDs has provided the widened light response, low recombination rate, and high charge transport in the DSSC structure. Graphical abstract: Image 1